Study to determine the knowledge attitudes and practices associated with menstruation and menstrual hygiene in adolescent school girls. - Fernando, W.M.P.A (My University, 2003)
The study revealed that mean age at menarche was 13 years, which is compatible with other studies done in Sri Lanka. The prior awareness about menstruation was not adequate and there was a strong association of mother as a source as well as preferred source of information about menstruation